Effective Supervision of Students' Activity During Classroom Learning and Testing - Szilágyi, Szabolcs (Acta Cybernetica, 2025)
Due to the lockdowns caused by the COVID-19 pandemic, the majority of educational institutions worldwide have been forced to switch to online education, which has created a significant challenge for teachers and students alike. In order to communicate effectively in the online space, educational institutions had a wide range of tools to choose from (e.g. Adobe Connect, Cisco Webex, Google Meet, Microsoft Teams, Skype, Zoom, etc.). The challenge for teachers was to learn how to use them, to teach practical subjects effectively and to provide a supervised examination environment. The return to face-to-face (in-class) teaching after the end of the COVID-19 pandemic has allowed the online collaborative environments listed above to fade into the background, but the supervision of interactive, computer-based practical lessons (e.g. teaching programming languages, network programming etc.) and proctored examinations can still be a challenge for teachers. This article reviews some screen monitoring systems developed for both corporate and educational environments. We present one of them in more detail, namely Veyon, which is available free of charge\footnote{The basic version of Veyon is free, but you have to pay for the various desired add-on licenses.} and can be used on different operating systems, and whose applicability in both teaching and examination has been tested for almost a year at the Faculty of Informatics of the University of Debrecen.